International Teaching Assistants in the Composition Classroom: From World Englishes to Translingualism and Beyond. Issue 3 (4th May 2019) - Kasztalska, Aleksandra
ABSTRACT: Although a significant body of research exists on Nonnative English Speaking Teachers (NNESTs) of composition, research on International Teaching Assistants (ITAs) of composition is rather limited. Few studies explore the training of composition ITAs or their experiences and professional identities, leaving open the question of how ITAs are influenced by discourses that frame native speakers as ideal English teachers and by alternative discourses that intend to empower NNESTs. Through focus groups, interviews, and short questionnaires, this study investigates the experiences of ITAs who teach composition at a large Midwestern university. The participants discuss their linguistic insecurities, their strengths and successes, and the role of World Englishes in shaping their professional identities and practice. The results of the study are discussed in the broader context of internationalization of higher education and in reference to translingualism and other alternative approaches to composition. Also discussed are implications for ITA training and preparation.